Infections after Anterior Cruciate Ligament Reconstruction: Which Antibiotic after Arthroscopic Debridement? - Pérez-Prieto, Daniel; Trampuz, Andrej; Torres-Claramunt, Raúl; Eugenia Portillo, María; Puig-Verdié, Lluís; Monllau, Joan C. (The Journal of Knee Surgery, 2017)
Arthroscopic debridement has proven to be the optimal surgical treatment for infections of the anterior cruciate ligament reconstruction (ACLR). Nevertheless, there are no reported data for the best antibiotic treatment option and its duration. The purpose of this article is to assess the usefulness of oral levofloxacin and rifampicin for the treatment of acute infections of an ACLR. This is a retrospective observational cohort study of patients operated on for ACLR over 4 years. A diagnosis of septic arthritis was based on patients' anamnesis and physical examination, laboratory parameters, and cultures of synovial fluid and/or joint tissue. Arthroscopic lavage was performed as soon as possible and tissue samples were taken. At a minimum 2-year follow-up, the infection was considered cured with a normal C-reactive protein (CRP) level and a correctly functioning and pain-free knee. Of the 810 patients, 15 (1.8%) were diagnosed as having an infection. Among the 13 staphylococcal cases (86.6%), 10 were susceptible to both quinolones and rifampicin (76.9% of the staphylococcal infections). There were two staphylococci that were rifampicin resistant. In the remaining one case, the coagulase-negative staphylococcus (CNS) was resistant to quinolones. One CNS infection was treated with linezolid and rifampicin and was the only case that needed graft removal due to treatment failure. Antibiotic treatment lasted an average of 6 weeks and oral treatment started at a mean of 5 days (range, 4–7). In the remaining 12 patients, CRP levels returned to normal at a mean of 3 weeks with good knee function and no local symptoms. Staphylococci (especially CNS) are responsible for almost 90% of acute ACLR infections in the current series. For the first time, the combination of levofloxacin and rifampicin is being proposed as a treatment in cases of an acute staphylococcal infection of an ACLR. An early switch to oral antibiotic treatment (as soon as the cultures are available) with both levofloxacin and rifampicin for a total (empiric and directed) period of 6 weeks should be considered as treatment of choice in acute staphylococcal infections of the ACLR with a retained graft. The level of evidence is IV (case series).
Keywords: anterior cruciate ligament; biofilm; rifampicin; knee infections; arthroscopic debridement; septic arthritis